Revising the link between microsaccades and the spatial cueing of voluntary attention. (April 2017) - Meyberg, Susann; Sinn, Petra; Engbert, Ralf; Sommer, Werner
Highlights: Microsaccades (MS) reflect two attention mechanisms during covert attention shifts. MS align with the direction of a cued shift of voluntary attention. MS align with the location of the cue symbol indicating the attention shift. MS alignment with cue location was four times stronger than with the cued shift. Both attention mechanisms were simulated in a computational model on MS generation. Abstract: Microsaccades – i.e., small fixational saccades generated in the superior colliculus (SC) – have been linked to spatial attention. While maintaining fixation, voluntary shifts of covert attention toward peripheral targets result in a sequence of attention-aligned and attention-opposing microsaccades. In most previous studies the direction of the voluntary shift is signaled by a spatial cue (e.g., a leftwards pointing arrow) that presents the most informative part of the cue (e.g., the arrowhead) in the to-be attended visual field. Here we directly investigated the influence of cue position and tested the hypothesis that microsaccades align with cue position rather than with the attention shift. In a spatial cueing task, we presented the task-relevant part of a symmetric cue either in the to-be attended visual field or in the opposite field. As a result, microsaccades were still weakly related to the covert attention shift; however, they were strongly related to the position of the cue even if that required a movement opposite to the cued attention shift. Moreover, if microsaccades aligned with cue position, we observed stronger cueing effects on manual response times. Our interpretation of the data is supported by numerical simulations of a computational model of microsaccade generation that is based on SC properties, where we explain our findings by separate attentional mechanisms for cue localization and the cued attention shift. We conclude that during cueing of voluntary attention, microsaccades are related to both – the overt attentional selection of the task-relevant part of the cue stimulus and the subsequent covert attention shift.